Substate Actor and Implementation of Sustainable Development Goals: Bandung City’s Paradiplomacy Practices in Water Leakage - Primawanti, Henike; Dermawan, Windy; Rahman, Sri Vania; Khurrahman, Zahra Afifah (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The paper aims to analyze the efforts Bandung City at the international level to improve its capabilities in reducing the level of water leakage as relevant to point 6 of the SDGs. The research method in this paper is a qualitative method with data collection through interviews with several relevant observations and field research through direct and documentary studies. This research found that paradiplomacy of Bandung City with the Japanese City of Hamamatsu came to cooperate in water leakage to implement SDG 6 in Bandung. Paradiplomacy of Bandung City turns into providing capacity-building programs to reduce the level of air leakage in Bandung City by optimizing clean water services. The collaboration between Bandung City Government and Hamamatsu City Government is not only in the process of technology transfer but also in exchanging knowledge and insights regarding water leakage. This conclusion concludes that implementing SDG 6 for local governments can be optimized with paradiplomacy to assist countries and regions in solving specific problems like Bandung City Government. The city of Bandung supports the SDGs point 6 program to reduce the problem of water leakage and the efforts coming from paradiplomacy.